2004
DOI: 10.1136/thx.2003.007542
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of criteria for selection of donor lungs suitable for transplantation

Abstract: Background: Donor organ shortage severely limits lung transplantation as a therapeutic option, yet many potential donor lungs are deemed unsuitable by clinical selection criteria. Methods: Of 39 consecutive potential donor lungs, 14 were accepted and 25 excluded by clinical selection criteria. All were evaluated prospectively by clinical assessment, bronchoscopy, and bronchoalveolar lavage (BAL) to evaluate objectively the discrimination of pulmonary infection and injury. Results: Accepted donors were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
0
30
1
Order By: Relevance
“…Current selection criteria are poor discriminators of pulmonary injury and infection and lead to the exclusion of potentially usable donor lungs (38). We (38) and others (16) have reported that physiological parameters in the donor, combined with AFC, could increase the rate of successful organ usage.…”
Section: Discussionmentioning
confidence: 99%
“…Current selection criteria are poor discriminators of pulmonary injury and infection and lead to the exclusion of potentially usable donor lungs (38). We (38) and others (16) have reported that physiological parameters in the donor, combined with AFC, could increase the rate of successful organ usage.…”
Section: Discussionmentioning
confidence: 99%
“…The internationally accepted selection criteria of the 'optimal donor' are primarily opinion based rather than evidence based, and their accuracy in determining the physiological status of the donor lung and predicting post-operative lung function is not optimal. 18 Fisher et al 19 have shown that current clinical donor lung assessment criteria are poor predictors of existing inflammation or infection in the donor lung, suggesting that many donor lungs deemed unusable may be unnecessarily excluded. Ware et al 20 evaluated 29 pairs of unusable lungs by physiological, microbiological and histological methods, and concluded that as many as 40% of these lungs would have been potentially suitable for transplantation.…”
Section: Assessment Of Donor Lung Usabilitymentioning
confidence: 99%
“…(8,88) Recommendation -Positive culture results or a clinical infection diagnosis should not lead to an absolute contra-indication of organ donation, nor should the deceased donor's maintenance be discontinued (D) (31) (B). (89,90) Strong Recommendation.…”
Section: Infection Aspectsmentioning
confidence: 99%
“…From the accepted donors, 75% had positive BAL cultures, and only 43% of the rejected donors had positive culture results (B). (89) Despite the severity of several microorganism infections, the literature reports on donors with Acinetobacter baumannii bacteremia and septic shock whose organs were successfully transplanted with preand post-transplant antibiotic therapy support, with no additional recipient morbidities (B). (90) When donor risk scores combined with receptor risk scores are analyzed for renal transplants, hepatitis C appears to be an independent rejection factor (B).…”
Section: When Is Infection a Contra-indication For Transplant?mentioning
confidence: 99%